Establishing a Payment Culture for Municipal Services in the North West Province: A Conceptual Framework - Enwereji, Prince Chukwuneme; Potgieter, Marius (International Journal of Economics and Financial Issues, 2018)
Payment for municipal services by residents in municipalities of the North West province is a challenging issue as consumer debt keeps on accumulating despite measures taken by the municipal role players to curb escalating accruals. The purpose of this study was to device a conceptual framework to disclose innovative measures municipalities can consider in their endeavor to establish a responsible payment culture for the payment of municipal services. The systems, contingency and social contract theory underpins this study. This study anticipates to find how the effective application of factors such as fiscal exchange, policies and legislation, service administration and measurement, payment knowledge and education, budget transparency, social influence and deterrence messages influence the payment culture for municipal services. In addition, the study proposes that the collaboration of traditional leaders (and other influential persons or groups) and municipal role-players, and also the application of emerging innovations and communication options could contribute towards establishing a favourable payment culture. This study also suggests that municipalities should uphold the prescripts of strategic management and strategic leadership in order to be visionary, dynamic, goal oriented, transformational and tactical to manage payment culture and strategy conflict. Keywords: Payment Culture, Strategic Management, Strategic Leadership, Payment Compliance JEL Classifications: D83, H63